Aesthetics after Darwin : the multiple origins and functions of art - Menninghaus, Winfried (Evolution, cognition, and the arts., 2019)
The book reveals a strong humanist heritage which renders Darwin's theory of song and poetic language far more nuanced and interesting than a monolithic ""singing for sex"" hypothesis.